Investigation of the long-term stability of quartzite and basalt for a potential use as filler materials for a molten-salt based thermocline storage concept. (1st September 2018) - Martin, Claudia; Bonk, Alexander; Braun, Markus; Odenthal, Christian; Bauer, Thomas
Highlights: Characterization of quartzite and basalt varieties as potential filler materials. Isothermal test at 560 °C in Solar Salt with a maximum duration of 10000 h. Determination of the stone microstructure by QEMScan before and after thermal test. DCS measurements of melting temperature and enthalpy of Solar Salt after thermal test. Ion chromotography measurements of salt composition of Solar Salt after thermal test. Abstract: Solar thermal power plants with integrated thermal storage are candidates for renewable energy production concepts. For cost reduction of thermal energy storage a single tank concept, the so called thermocline storage concept, instead of the two-tank molten salt thermal storage is as promising cost reduction option. Further cost reductions in the thermocline storage are expected by replacing a significant amount of Solar Salt by a low cost filler material. Such filler materials have to be stable in molten salt at temperatures up to 560 °C. In this work degradation studies on quartzite and basalt types in molten salt are carried out after a preselection has been published elsewhere recently. The investigations are focused on the compatibility of natural stones with Solar Salt, a mixture of sodium nitrate and potassium nitrate, as common heat storage material. This work addresses changes of the molten salt properties and in the microstructure of the natural stones depending on the exposure time in molten salt at temperatures of approximately 560 °C. In the first step of the material investigation the natural stones were isothermally stored in Solar Salt at a maximum temperature of 560 °C for up to 10.000 h. After the thermal treatment the microstructure of the stones was investigated by QEMSCAN (Quantitative Evaluation of Minerals by Scanning electron microscopy). By means of this analysis method the changes in the microstructure of quartzite and basalt was detected and arising stone components are identified. The melting temperature und enthalpy of Solar Salt was measured and compared with the salt properties before the thermal treatment. Additionally, the specific heat capacities of basalt and quartzite depending on the temperature were determined. The results are essential to verify the suitability of quartzite and basalt as potential filler materials in modern thermocline storage concepts.